(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This study investigates e-learning and its importance nowadays and in the future using a test and statistical analysis to prove that scientifically. E-learning or Electronic learning is the delivery of teachingand training through digital resources. Although e-learning is based on formalized learning, it is provided through electronic devices such as computers and phones that are connected to the internet. The study aims at showing by percentages whether or not e-learning is important.Quantitative method is used to analyse a test and the results of the testshows that more than 80% of students see e-learning is indispensable and has great benefits in the future for many reasons that they will be shown later on in the research. The study consists of four chapters. The first chapter carries on the introduction of the current study as wellas tackling the problem of the study, the hypotheses and the value of the study. The second chapter includes literature review of e-learning.The third chapter carries on the data and its analysis through the test, as well as the statistical results. And finally chapter four tackles the conclusions.